Knowledge Analysis of Postnatal Mother about Essential Newborn Care with Incidence of Postpartum Blues: A Cross-Sectional Study - Ambarsarie, Riry; Prima, Indah; Sudjatmoko, Andri (Universitas Muhammadiyah Yogyakarta, 2024)
Stress in the postpartum period can cause anxiety, fatigue, and decreased self-care associated with an increased risk of postpartum depression. In Indonesia, the incidence of postpartum blues is between 50-70%. This study assessed knowledge of essential newborn care among postnatal mothers and identified the incidence rate of postpartum blues. This cross-sectional study was conducted in Bengkulu city. Respondents of this research were 57 mothers who met the criteria included in the 2 weeks postpartum in Public Health Facilities. Mother’s knowledge was measured by Essential Newborn Care Questionnaire. The symptoms of postpartum blues were measured by the Edinburg Postnatal Depression Scale (EPDS). The contingency coefficient shows a relationship between mother’s knowledge about essential newborn care and the incidence of postpartum blues (p = 0.002; r = 0.380). The multiple logistic regression proved that knowledge is the main risk factor of postpartum blues (p 0.007; OR 6.039). The results of this study indicate that there is a significant relationship between maternal knowledge about essential newborn care and postpartum blues with a weak relationship. Those with poor knowledge, who are 6.039 times more risky than those with good knowledge, should be targeted for newborn care education.